Analysis of the outer surface geometry on drawn tubes - Gorog, Augustin; Gorogova, Ingrid (Manufacturing Technology Journal, 2020)
Technological conditions of tube drawing influence the properties of the resulting products. In addition to mechan-ical properties, they also affect the geometry of the drawing tube ? macro geometry and microgeometry. The paper presents the results of measurements of macro geometry (roundness and cylindricity) and micro geometry (surface roughness) of the outer surface of the drawn tube. Tubes (STN 41 1353) were drawn through dies with different reduction angles (6° and 12°). On used fixed mandrels were ground the straight and spiral grooves. The effect of these grooves and hence the deformation itself has also been manifested on the outer surface of the drawn tube. On the measured roundness profiles are significantly noticeable places where the land and the groove were when drawing. This effect can also be observed on the deteriorated measured values of roundness. On the meas-ured values and roughness profiles of the outer surface of the drawn tube can also be observed the difference be-tween land and grove.
Keywords: drawn tubes; roundness; cylindricity; surface roughness